Modelldurchgängigkeit in der Prozessindustrie am Beispiel virtueller Inbetriebnahme1. Issue 11 (14th September 2017) - Yakut, Nataliya; Krüning, Kai; Foltin, Gregor; Burger, Jakob; Krauss, Michael; Asprion, Norbert; Bortz, Michael; Roth, Matthias
Abstract: In current industrial practices, different simulation tools are used throughout the life cycle of a process plant. However, there is no continuous use of these tools available so far. Especially, reuse of the process models is strongly limited. Therefore, in this work we developed a technique, that enables the creation of dynamic mid‐fidelity models from already existing steady‐state high‐fidelity ones in a systematical and efficient way. These models can be used in later phases of the life cycle for virtual commissioning of automation applications.